(Natlas ANATOMII ^ELOWEKA (B2 (NTOMs (Nu^EBNIKs - (Nr(B,(Nd(B,(NsINELXNIKOWs; (NsINELXNIKOW q(B.(Nrs; (NsINELXNIKOW a(B.(Nqs ((NmOSKWAs (NiZDATELX uMERNIKOWs, 2009)
(NwO WTOROM TOME RASSMATRIWA@TSQ U^ENIE O WNUTRENNOSTQH(B- (NPI]EWARITELXNOJ T DYHATELXNOJ(B. (NMO^EWOJ I POLOWYH SISTEMAH A TAKVE \NDOKRINNYE VELEZY s
Keywords: (Natlas ANATOMII ^ELOWEKA (B2 (NTOMs